HUBUNGAN PEMBERDAYAAN PEGAWAI DENGAN PENINGKATAN PRODUKTIVITAS PEGAWAI (STUDI KASUS PADA BAGIAN FIBER DAN RADIO ACCESS MAINTENANCE PT. TELEKOMUNIKASI BANDUNG) - Widayanti, Widayanti (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
The empowerment in the Section of Fiber and Radio Access Maintenance PT. Telecomunication Bandung has not fully well practiced. It seems the Head has done less effort to support the implementation of empowerment, as indicated in less opportunity given to the workers to consult about work either formally or informally and no recognition or reasonable reimbursement for workers with a good achievement. The Head has infrequently delegated the authority for decision making to lower managers while the head is away. Therefore, some suggestions are proposed as folllows: the Head of Section of Fiber and Radio Access Maintenance PT. Telecomunication Bandung should conduct either formal or informal annual staff meeting involving all workers to discuss the problems in accomplishing work duties and to find the solution over problems. The Section of Fiber and Radio Access Maintenance PT.Telecomunication Bandung should give an orientation for aa workers concerning precise job description, applicable work procedure, and the sequence of work management, procedure, and system that enable all workers to complete the duties and to achieve the work effectiveness.